1979
DOI: 10.1007/bf00119193
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic matching of superconducting films to substrates

Abstract: Acoustic mismatch theory is used to estimate phonon transmission coefficients for various superconductor/substrate interfaces. It is shown that the conventionally employed substrates offer the largest acoustic mismatch to many of the commonly studied superconductors, thereby leading to unnecessarily large phonon-trapping and other nonequilibrium effects. Most available experimental results are shown to be in reasonable agreement with the theoretical estimates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
118
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(123 citation statements)
references
References 27 publications
5
118
0
Order By: Relevance
“…The phonon escape time τ e = 8.96 ns = 34τ φ was set to maintain power balance for the absorbed optical power for ≈ 15%. This value is about an order of magnitude larger than the equivalent value used by Goldie and Withington 31 and de Visser et al 13 , however it is within the range of reported values for τ e for Al on sapphire 37 . We found that relatively large changes in τ e resulted in relatively small changes in σ 1 and σ 2 .…”
Section: Quality Factor and Frequencysupporting
confidence: 54%
See 2 more Smart Citations
“…The phonon escape time τ e = 8.96 ns = 34τ φ was set to maintain power balance for the absorbed optical power for ≈ 15%. This value is about an order of magnitude larger than the equivalent value used by Goldie and Withington 31 and de Visser et al 13 , however it is within the range of reported values for τ e for Al on sapphire 37 . We found that relatively large changes in τ e resulted in relatively small changes in σ 1 and σ 2 .…”
Section: Quality Factor and Frequencysupporting
confidence: 54%
“…Here τ e is the escape time for phonons to leave the superconductor and go into the substrate 37 . We use a version of the Parker heating model 35 and set (4) Although n opt takes the form of a Bose-Einstein thermal distribution with effective temperature T eff for Ω > 2∆, it is not a thermal distribution since n opt = 0 for Ω < 2∆.…”
Section: Loss From Nonequilibrium Distribution Of Quasiparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…For our 80-nm bi-layer Al film on sapphire, the best estimate of F is in the range of 5-10 considering the strong acoustic mismatch at the interface 40 . The reported values of r for Al in the literature range from 1/(120 ns) to 1/(8 ns) 14,18,19,28,41 .…”
Section: Qp Recombination Constant Across Seven Devices (Supplementarymentioning
confidence: 99%
“…The phonon distribution in the substrate n sub ðΩÞ is assumed to have a Bose-Einstein distribution at the bath temperature T bath . τ esc ¼ 0.17 ns is the phonon escape time, calculated for Al on sapphire using the acoustic mismatch model [26]. N ion is the number of ions per unit volume and DðΩÞ ¼ 3Ω 2 =Ω 3 D is the phonon density of states.…”
mentioning
confidence: 99%